TUTURAN PERSUASIF USTAZ FIKRI MZ DALAM CERAMAH ISLAM - Sinaga, Mangatur; ', Misfardi; ', Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to describ the form of persuasive speech and persuasive techniques that is used by Ustaz Fikri MZ in Islamic discourse. This research is qualitative descriptive study. The object of this research is the persuasive speech of Ustaz Fikri MZ. The data ware obtained by using see-record techniques and the four video documentation of Ustaz Fikri MZ. The result of this research is the form of classification persuasive speech and persuasive techniques of Ustaz Fikri MZ in Islamic discourse. Based on the analysis of the data, the form of persuasive speech that are used by Ustaz Fikri MZ are: (1) assertive, (2) directive, (3) commissive, (4) expressive, and (5) declarative. Meanwhile, the persuasive techniques that are used are: (1 ) direct persuasive, (2) indirect persuasive, (3) reference- persuasive (4) criterion- persuasive, (5) cause-effect persuasive (6) figure speech persuasive, (7) analogy persuasive, and (8) threats-persuasive.Keys words: persuasive speech, persuasive speech forms, persuasive techniques.